Zero tolerance starts now: Making nurses' safety a priority. Issue 11 (November 2021) - Stand, Lisa; Francis, Ruth; Bickford, Carol J.; Boston-Leary, Katie
Abstract : This article provides an overview of how policymakers define workplace violence in healthcare; reviews some of the strategies recommended for prevention; and offers concrete suggestions and tools for nurse leaders, recognizing the ongoing challenges of the COVID-19 pandemic.